Educación jurídica internacional - Kennedy, David (2010)
"Originally published as International Legal Education, in 26 Harv. Int'l L. J. 361 (1985). Translation by Public Translator Romina Redondo. The editors gratefully acknowledge the generosity of the author and the authorities of the Harvard International Law Journal in allowing the translation and reproduction of the article."